Advances in Management and Applied Economics 2023
DOI: 10.47260/amae/1325
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Impact of Green Credit on Financial Performance of China’s Listed Banks

Abstract: The concept of green environmental protection and sustainability is deeply rooted in China. Green credit has become an important social issue in recent years. Most Chinese financial institutions are also actively participating and investing in this field, especially banks. In order to explore the correlation between banks' participation in green credit business and banks' financial performance, this paper collects the green credit balance, green credit ratio, return on total assets, non-performing loan ratio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Wang and Zhou [5] used ROE indicators to test and found that non-interest income significantly reduced the net asset income, which had a negative effect on the business performance of commercial banks. Dai and Luo [6] found that commission and commission income have a positive effect on bank performance, while their investment income is the opposite. Tong.…”
Section: Journals Reviewedmentioning
confidence: 99%
“…Wang and Zhou [5] used ROE indicators to test and found that non-interest income significantly reduced the net asset income, which had a negative effect on the business performance of commercial banks. Dai and Luo [6] found that commission and commission income have a positive effect on bank performance, while their investment income is the opposite. Tong.…”
Section: Journals Reviewedmentioning
confidence: 99%
“…The increased leverage ratio will have a positive impact on banks' technical efficiency and return on assets. At the same time, it will reduce their NPL (Non-performing Loan) and loan-to-deposit ratio, enhancing their ability to resist risks and facilitating stable operation Yuan, 2023).…”
Section: Mechanism Assumptionsmentioning
confidence: 99%